2009
DOI: 10.1016/j.ejphar.2009.05.022
|View full text |Cite
|
Sign up to set email alerts
|

A cembranoid from tobacco prevents the expression of nicotine-induced withdrawal behavior in planarian worms

Abstract: Using an adaptation of published behavioral protocols, we determined that acute exposure to the cholinergic compounds nicotine and carbamylcholine decreased planarian motility in a concentration-dependent manner. A tobacco cembranoid (1S,2E,4R,6R,7E,11E)-cembra-2,7,11-triene-4,6-diol (4R-cembranoid), also decreased planarian motility. Experiments in the presence of 1 μM 4R-cembranoid did increase the IC 50 for nicotine-but not carbamylcholine-induced decrease in planarian motility. When planarians were exposed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 50 publications
4
47
0
2
Order By: Relevance
“…Reference [24] did not specify the chemical form of (-) nicotine that they used. It is possible that the tartrate salt decreases the potency of nicotine, however, in previous work, we observed that tartrate by itself does not induce any observable behavior in planarians [4]. This is an intriguing discrepancy that warrants further investigation.…”
Section: Resultsmentioning
confidence: 80%
See 1 more Smart Citation
“…Reference [24] did not specify the chemical form of (-) nicotine that they used. It is possible that the tartrate salt decreases the potency of nicotine, however, in previous work, we observed that tartrate by itself does not induce any observable behavior in planarians [4]. This is an intriguing discrepancy that warrants further investigation.…”
Section: Resultsmentioning
confidence: 80%
“…Several studies have established the presence of cholinergic systems in planarians; acetylcholine and nicotine influence the behavior of these worms [3][4][5]. Candidate nicotinic acetylcholine receptor (nAChRs) examples have been found in planarians using various techniques including in situ hybridization [6], microarray technology [7] and expression sequence tags [8].…”
Section: Introductionmentioning
confidence: 99%
“…The use of these ceramic containers allowed us to minimize the amount of reagents used. Withdrawal-like behavior experiments were adapted from established protocols [5]. Planarians were placed individually in 1.5 mL microcentrifuge tubes with experimental solutions of either APW, 100 μM nicotine, 100 μM cotinine, or a combination of 100 μM nicotine/100 μM cotinine and were closed for 21-26 hours.…”
Section: Methodsmentioning
confidence: 99%
“…In planarians, nicotine displays an increase in motility at lower concentrations, a decrease in motility at higher concentrations, and an increase in planarian seizure like movements (pSLM) [10,11]. Planarians exposed to nicotine for a period of about 24 hours display a series of withdrawal-like behaviors [5]. …”
Section: Introductionmentioning
confidence: 99%
“…These flatworms utilize neurotransmitter systems, including glutamate, dopamine, serotonin, acetylcholine, and GABA (Nishimura et al, 2010) and display mammalian-like responses to drugs of abuse including abstinence-related withdrawal, behavioral sensitization, and enhanced stereotypical activity (Pagán et al, 2009; Kusayama and Watanabe, 2000; Palladini et al, 1996). A tendency to spend less time in light versus dark environments is a behavioral phenotype of planarians (Zhang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%